ENHANCING STUDENT SKILLS THROUGH SHOOTING TRAINING (World Bulletin of Management and Law, 2023)
This annotation explores the concept of teaching shooting training to students, focusing on the development of skills, safety considerations, techniques, and the importance of practice and accuracy. It highlights the significance of incorporating proper education and instruction in firearms handling, emphasizing safety protocols and responsible behavior. The annotation also discusses the role of technique in improving shooting accuracy and the benefits of practical training methods. It provides a foundation for understanding the complexities involved in teaching shooting skills to students, promoting their physical and mental development, while prioritizing safety and ethical considerations